The control system for radiation sterilization of health-care products at the accelerator LU-10 - Boriskin, V.N.; Dovbnya, A.N.; Karasyov, S. P.; Nikiforov, V.I.; Pomatsalyuk, R.I.; Tenishev, A.Eh.; Uvarov, V.L.; Shevchenko, V.A.; Shlyakhov, I.N. (Вопросы атомной науки и техники, 2006)
The regulatory documents for the technological process of sterilization (DSTU ISO 11 137:2003 and others) set requirements on monitoring, maintaining and archiving the basic parameters of the process. To meet the requirements, an automated control system was created at the LU-10. It includes a PC-controlled beam scanner, technological measuring channels (TMC), and also a set of working standards to calibrate the channels. The CAMAC standard was used as an interface. The software of the complex provides the real-time processing of information on the beam parameters, their control, archiving, and also the information exchange within the local-area technological network. The presence of the Customer Database comprising the characteristics of incoming products makes it possible to optimize the process conditions for the products by the computer simulation method. Нормативные документы на технологический процесс стерилизации (ДСТУ ISO 11 137:2003 и др.) устанавливают требования мониторирования, поддержания и архивирования основных параметров процесса. Для удовлетворения этим требованиям на ЛУ-10 создана автоматизированная система контроля. В ее состав входит управляемый РС сканер пучка, технологические измерительные каналы, а также набор рабочих эталонов для калибровки каналов. В качестве интерфейса использован стандарт КАМАК. Программное обеспечение комплекса дает возможность в режиме реального времени производить обработку информации о параметрах пучка, управлять ими, их архивировать, а также обмениваться информацией в пределах локальной технологической сети. Наличие базы данных «Заказчик» с характеристиками поступающей продукции позволяет оптимизировать режим ее обработки методом компьютерного моделирования. Нормативні документи на технологічний процес стерилізації (ДСТУ ISO 11 137:2003 та інші) установлюють вимоги моніторування, підтримки і архивування основних параметрів процесу. Для задоволення цим вимогам на ЛП-10 створена автоматизована система контролю. У її склад входить керований РС сканер пучка, технологічні вимірювальні канали, а також набір робочих еталонів для калібрування каналів. Як інтерфейс використаний стандарт КАМАК. Програмне забезпечення комплексу дає можливість у режимі реального часу робити обробку інформації про параметри пучка, керувати ними, архивувати їх, а також обмінюватися інформацією в межах локальної технологічної мережі. Наявність бази даних «Замовник» з характеристиками продукції, що надходить, дозволяє оптимізувати режим її обробки методом комп'ютерного моделювання.